ANÁLISE E RELEVÂNCIA DOS DADOS DE ESTABILIDADE ADICIONAIS DO NIVESTIM™ (FILGRASTIM SOLUÇÃO INJETÁVEL) - António de Melo Gouveia (Formifarma, LDA., 2012)
The most recent data about stability of fligrastim biossimilar ("Nivestim™), as made available by the marketing authorization holder, is analyzed with a focus on different storage conditions and impact on real life use, both for patients and healthcare professionals. Data assessed is about 3 batches and 2 strengths of the Nivestim ™, which were studied 8 months after end of approved shelf-life. The drug product was stored at 25ºC+-2ºC for 7 days, with and without light exposure. Freeze - thaw studies were also performed. As a control, samples were kept in storage conditions as stated on the approved summary of product characteristics. The parameters analyzed were stable with no appreciable trends during the time and in the conditions of this study. This data allows a drug product more adapted to real life use, with advantages for both patients and healthcare professionals.